Copper(Ii) Salicylaldehyde-N,N-Dibenzylsemicarbazone – A Potential Antitumour Compound - PETER PENG FOO LEE; KENNETH K POON (International Journal of Pharma and Bio Sciences, 2011)
From QSAR studies, a series of salicylaldehyde semicarbazones, HOC6H4CH=N‑NHCONR2 (H2R2) and their Cu(II) complexes were synthesized, characterized and investigated for their biological activities previously. Results obtained showed that one of the most active compounds in this series is [Cu(HBnz2)Cl]. Thus, in this study, research was then carried out to investigate the anti-tumour property of this compound. The LD50 of [Cu(HBnz2)Cl] was determined to be at 75 mg/kg. Anti-tumour property was observed when this compound was introduced to tumours of human origin (MOLT-4 on SCID mice) and murine origin (3LL on normal mice).